Evident sexual dimorphism in the shape of subadults of astyanax altiparanae (teleostei, characidae) (2022)
The fish species known as “lambari” inhabit small streams, lakes, and large rivers throughout the entire tropical environment of the New World; however, there is limited quantitative information regarding its morphological variations. Our investigation was aimed at studying the sexual dimorphism in subadults of Astyanax altiparanae, using geometric morphometrics to compare sexes in terms of not only size (height and weight) but also shape. A total of 47 specimens (34 males and 13 females) was randomly collected. Photographs of the lateral plane were obtained without sacrificing the specimens, and eight landmarks were placed in the images. The results showed statistically significant differences between sexes. The length of the snout and thickness of the abdomen and caudal peduncle were greater in females, whereas males presented greater dorsal curvature. Females had tall and robust bodies, whereas males were longer and thinner. The difference in shape is probably associated with the species' defensive or survival strategies. However, whether there are ecological advantages or behavioral aspects in sexual dimorphism is still poorly understood, and further research is required to provide data that can explain the causes.